Making sense of soft information: interpretation bias and loan quality - Campbell, Dennis; Loumioti, Maria; Wittenberg-Moerman, Regina (Journal of Accounting and Economics, 2019)
We explore whether cognitive constraints and behavioral biases impede the processing and interpretation of soft information in private lending. Using data from a credit union's internal reporting system, we delineate three constraints and biases likely to affect lending decisions: limited attention, task-specific human capital and common identity. We find that soft information leads to worse loan quality when loan officers are busy or before weekends and around national holidays; when they have prior sales experience; and when both the officers and borrowers are men. We provide evidence of non-agency-related costs in the use of soft information in lending decisions.